The Malay-Muslim insurgency in southern Thailand : understanding the conflict's evolving dynamic : RAND counterinsurgency study--paper 5 - Chalk, Peter; Rand eBooks (Santa Monica, CA : RAND, 2008)
Current unrest in the Malay-Muslim provinces of southern Thailand has captured growing national, regional, and international attention due to the heightened tempo and scale of rebel attacks, the increasingly jihadist undertone that has come to characterize insurgent actions, and the central government's often brutal handling of the situation on the ground. Of particular note are growing concerns that the conflict is no longer purely local in nature but has been systematically hijacked by outside extremists to avail wider transnational Islamist designs in southeast Asia. No concrete evidence suggests that the region has been decisively transformed into a new beachhead for pan-regional jihadism. Although many of the attacks currently being perpetrated in the three Malay provinces have a definite religious element, it is not apparent that this has altered the essential localized and nationalistic aspect of the conflict. While the scale and sophistication of violence have increased, nothing links this change in tempo to the input of punitive, absolutist external jihadist imperatives. Perhaps the clearest reason to believe that the southern Thai conflict has not metastasized into a broader jihadist struggle, however, is the fact that there has been neither a migration of violence north nor directed attacks against foreigners, tourist resorts, or overt symbols of U.S. cultural capitalism.
Introduction -- The insurgency -- A new front in the global jihad? -- Conclusion: Future prospects.
"RAND National Defense Research Institute."
Includes bibliographical references (p. 23-27).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Insurgency -- Thailand, Southern; Islam and politics -- Thailand, Southern; Muslims -- Thailand, Southern -- Political activity; Thailand, Southern -- Politics and government -- 1988-; Electronic books